PERMAINAN TRADISIONAL DI ERA MODERN SEBAGAI SUMBER IDE PENCIPTAAN KARYA SENI LUKIS - Ita - Lusyani; Syamsiar Syamsiar Syamsiar (Texture: Visual Art and Culture Journal, 2023)
The creation of the Final Project entitled "Traditional Games in the Modern Era of Ideas in the Creating of Paintings" is taken from the current state of traditional games. There are several factors that cause traditional games to be abandoned today; 1). Reduced children's play area, 2). The role of parents, 3). Enter the modern game. At this time traditional games are rarely played by children, because most children are more interested in playing smartphones. The process of creating this final painting work uses the theoretical basis of L.H Chapman, which mentions 3 stages, namely, 1). Efforts to find ideas or find sources of ideas, inspiration, 2). Enchane, develop and establish initial ideas, 3). Visualization into the medium. Objects in paintings and figures for children are depicted with decorative naive forms and the choice of colors uses bright colors which are expected to be able to express an atmosphere of joy. The child figures experience a change in facial anatomy, which is expected to represent the character of a child who is innocent and free-spirited and depicts innocent children who have not yet found their identity. In this painting, the author displays the atmosphere that occurs in each of his paintings.